A RARE FORM OF MYOCARDIAL INFLAMMATION – COMPLICATIONS WITH A VENTRICULAR ASSIST DEVICE AND SUCCESSFUL TRANSPLANTATION - Marcin Schulz; Rafał Skowronek; Alexander Suchodolski; Jerzy Nożyński; Mariola Szulik (International Journal of Innovative Technologies in Social Science, 2025)
Giant cell myocarditis (GCM) is a rare, often fulminant inflammatory cardiomyopathy associated with rapid progression to advanced heart failure and high mortality. We report the case of a 52-year-old male with previously undiagnosed GCM who developed post-inflammatory cardiomyopathy leading to severe left ventricular dysfunction. Despite implantation of a cardiac resynchronization therapy defibrillator (CRT-D) and later a HeartMate III left ventricular assist device (LVAD) as a bridge to transplantation, the patient’s condition gradually worsened. Orthotopic heart transplantation was performed 5.5 years after diagnosis, with histopathological analysis of the explanted heart confirming GCM. Post-transplant follow-up over 16 months demonstrated preserved graft function, absence of recurrence, and stable clinical status. This case highlights the importance of histopathological evaluation of explanted hearts, the diagnostic challenges of atypical GCM, and the role of LVAD and heart transplantation in ensuring long-term survival. Video 1. Transthoracic echocardiography showing severely impaired left ventricular contractility with a left ventricular ejection fraction. Watch video